2012
DOI: 10.1002/jcb.24006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of pre‐replication complex proteins in transformed and normal cells

Abstract: This study examines the abundance of the major protein constituents of the pre-replication complex (pre-RC), both genome-wide and in association with specific replication origins, namely the lamin B2, c-myc, 20mer1, and 20mer2 origins. Several pre-RC protein components, namely ORC1-6, Cdc6, Cdt1, MCM4, MCM7, as well as additional replication proteins, such as Ku70/86, 14-3-3, Cdc45, and PCNA, were comparatively and quantitatively analyzed in both transformed and normal cells. The results show that these protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 86 publications
4
25
0
Order By: Relevance
“…Consistent with previous findings, we observed that 3 tumor-derived cell lines showed high ORC1 expression compared with nontumor lines (24)(25)(26)(27). In general, higher ORC1 levels were required to maintain viability in the tumor lines (although MRC-5 cells also had a requirement for a higher ORC1 level).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous findings, we observed that 3 tumor-derived cell lines showed high ORC1 expression compared with nontumor lines (24)(25)(26)(27). In general, higher ORC1 levels were required to maintain viability in the tumor lines (although MRC-5 cells also had a requirement for a higher ORC1 level).…”
Section: Discussionsupporting
confidence: 91%
“…Most tumor cells suffer high replication stress, due to uncontrolled proliferation and/or enhanced genomic instability. Interestingly, several studies have reported that origin-licensing proteins are overexpressed in tumor-derived cell lines (24)(25)(26)(27). Given this, we reasoned that tumor cells might have a greater demand for origin licensing than nontransformed cells, either to sustain rapid replication and/or to enhance recovery from the increased level of replication stalling/collapse.…”
Section: Significantly Mcm4mentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin Immunoprecipitation (ChIP) Assays-Cells cultured in complete media were washed with pre-warmed PBS and treated with 1% formaldehyde for 10 min to cross-link proteins and DNA in vivo (56). They were then washed and scraped into ice-cold PBS and resuspended in lysis buffer (50 mM HEPES-KOH (pH 7.5), 140 mM NaCl, 1% Triton X-100, 2 mM EDTA) supplemented with a complete protease inhibitor tablet (Roche Applied Science).…”
Section: Methodsmentioning
confidence: 99%
“…53 Plk1 upregulation is so widespread in malignancies that it has been termed a 'general feature of human cancer.' 54 Although ORC1 and MCM5 display aberrant expression in certain transformed cells, 55 MCM5 is consistently upregulated in cancers and is considered a biomarker. 56,57 Much evidence also links deregulation of centrosome licensing factors with centriole overduplication.…”
Section: Excess Baggage: How Cancer Cells Acquire Extra Centrosomesmentioning
confidence: 99%